Epidemiology and Risk Factor Analysis of Systemic Allergic Reaction to Bee Venom in the Slovenian Population of Beekeepers - CARLI Tanja; LOCATELLI Igor; KOŠNIK Mitja; BEVK Danilo; KUKEC Andreja (Slovenian Journal of Public Health)
To estimate the lifetime prevalence of first and recurrent systemic allergic reaction to bee venom among Slovenian beekeepers. Additionally, we aimed to elucidate the risk factors predisposing beekeepers to developing systemic allergic reaction to bee venom.